Efficient implementation of structure-aware private set intersection protocol - Shi, Zhengyu (Nanyang Technological University, 2024)
This research aims to producing an efficient, secure and modern implementation of a Structure-Aware Private Set Intersection protocol. Private Set Intersection (PSI) is a fundamental problem in cryptography and privacy computing that aims to securely finding intersection of two parties' sets without disclosing contents beyond intersection to any of the parties. Our work implements three recipes of Structure-Aware PSI under the GRS22 framework with modern C++, and perform rigorous tests and benchmarks over the recipes under different parameter set and settings.